A systematic screen for proteing-lipid interactions in Saccharomyces cerevisiae - Gallego, Oriol; Betts, Matthew J.; Gvozdenovic-Jeremic, Jelena; Maeda, Kenji; Matetzki, Christian; Aguilar-Gurrieri, Carmen; Beltran-Alvarez, Pedro; Bonn, Stefan; Fernández-Tornero, Carlos; Jensen, Lars Juhl; Kuhn, Michael; Trott, Jamie; et al. (Molecular Systems Biology, 2010)
Proteing-metabolite networks are central to biological systems, but are incompletely understood. Here, we report a screen to catalog proteing-lipid interactions in yeast. We used arrays of 56 metabolites to measure lipid-binding fingerprints of 172 proteins, including 91 with predicted lipid-binding domains. We identified 530 proteing-lipid associations, the majority of which are novel. To show the data set's biological value, we studied further several novel interactions with sphingolipids, a class of conserved bioactive lipids with an elusive mode of action. Integration of live-cell imaging suggests new cellular targets for these molecules, including several with pleckstrin homology (PH) domains. Validated interactions with Slm1, a regulator of actin polarization, show that PH domains can have unexpected lipid-binding specificities and can act as coincidence sensors for both phosphatidylinositol phosphates and phosphorylated sphingolipids. © 2010 EMBO and Macmillan Publishers Limited All rights reserved.